Efektivitas Kunyit Asam Dalam Mengatasi Dismenorea Pada Remaja (Studi Kasus Siswi Kelas X SMK Az-Zawiyah Tanjung Batu) - ., Miranti; ., Wijaya; Ilyas , Deddy (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This thesis is entitled "Effectiveness of Tamarind Turmeric in Overcoming Dysmenorrhea in Adolescents (Case Study of Class sequential exploratory. A sample of 8 female students who experienced severe dysmenorrhoea were divided into 2 groups, 4 in the experimental group and 4 in the control group. The research instrument used (NRS). Data collection techniques in this research used observation, interviews and documentation methods. Research data was analyzed using the visual inspection method and qualitative descriptive techniques. The formulation of the problem in this research is how the Prophet's style of treatment relates to traditional treatment using sour turmeric drinks for dysmenorrhoea and whether there is an effect of giving sour turmeric drinks on reducing dysmenorrhoea in grade 10 female students at SMK Az-Zawiyah Tanjung Batu. The results of this research are 1) Habbatussauda, ​​which is included in the Prophet's style of treatment, can reduce the level of dysmenorrhoea because it has anti-inflammatory and analgesic properties. It is used as a reference for reducing the level of dysmenorrhoea in adolescents using herbal plants that grow in Indonesia and have anti-inflammatory and analgesic properties, namely turmeric and tamarind. . Where when processing sour turmeric drinks, honey is mixed which functions to reduce the chelating taste of turmeric and reduce dysmenorrhoea, because honey contains enzymes and minerals that are effective in reducing pain. 2) There is an effect of sour turmeric drink on reducing dysmenorrhoea in grade 10 female students at Az-Azzawiyah Vocational School. Although the reduction in pain level was not drastic, namely from average level of severe pain to moderate level of pain.